1999
DOI: 10.2105/ajph.89.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and breast cancer screening among Hispanic women in New York City.

Abstract: OBJECTIVES: This study investigated whether acculturation was associated with the receipt of clinical breast examinations and mammograms among Colombian, Ecuadorian, Dominican, and Puerto Rican women aged 18 to 74 years in New York City in 1992. METHODS: A bilingual, targeted, random-digit-dialed telephone survey was conducted among 908 Hispanic women from a population-based quota sample. Outcome measures included ever and recent use of clinical breast examinations and mammograms. Multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
5
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 53 publications
2
99
5
1
Order By: Relevance
“…Latinas in the US underutilize mammography, 2,13,18,60,61 and foreign-born Latinas have even lower usage rates. 14,18,[62][63] However, the rate at which Latinas in our study underwent recent mammography (73%) was higher than that reported in a national study of Latinas (59%) [63][64] and much higher than rates in other studies of Latina immigrants (39-47%). 13 Our results may partially reflect the fact that most of the women had access to health care and/or health information and that the region includes several low-cost screening services.…”
Section: Discussionmentioning
confidence: 55%
“…Latinas in the US underutilize mammography, 2,13,18,60,61 and foreign-born Latinas have even lower usage rates. 14,18,[62][63] However, the rate at which Latinas in our study underwent recent mammography (73%) was higher than that reported in a national study of Latinas (59%) [63][64] and much higher than rates in other studies of Latina immigrants (39-47%). 13 Our results may partially reflect the fact that most of the women had access to health care and/or health information and that the region includes several low-cost screening services.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, our findings are similar to those in previous studies reporting that physician recommendation, acculturation and length of stay in the United States, and barriers to mammography were significantly associated with screening behavior. 16,25,37,[77][78][79][80][81][82][83][84] Self-efficacy is a key variable in the Health Belief Model (HBM). Interestingly, self-efficacy was significant in distinguishing between women who had never had a mammogram and those who had had at least one but was not a predictor for adherence to screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…14,62,63 Somewhat surprisingly, however, Dominican women also screened at equivalent rates, 64 a result that is inconsistent with some previous research. 30,65,66 The rates of the remaining immigrant groups-two of African descent and one of European descent-had odds ratios that differed significantly from the European-American comparison group. Before the entry of the cognitive and socioemotional variables, women from the English-speaking territories of the Caribbean, women from Haiti, and women from Eastern Europe were 55-74% less likely to be screened regularly compared with U.S.-born European Americans.…”
Section: Discussionmentioning
confidence: 99%